A new approach to classification of 40 years of Antarctic sea ice concentration data - Wachter, Paul; Reiser, Fabian; Friedl, Peter; Jacobeit, Jucundus (International Journal of Climatology, 2020)
In this paper, we present a characterization of Antarctic sea ice based on the classification of annual sea ice concentration (SIC) data from 1979 to 2018. A clustering algorithm was applied to provide a climatological description of significant annual cycles of SIC and their spatial distribution around the Southern Ocean. Based on these classification results, we investigate the variability of SIC cycles on decadal and inter-annual time scales. First, we discuss significant spatial shifts of SIC cycles during 1979–1998 and 1999–2018. In the Weddell Sea and in large parts of the Ross Sea, we observed higher SIC during the summer season, and an extension of sea ice cover in winter compared to the long-term average. Second, we introduce the Climatological Sea Ice Anomaly Index (CSIAI), which is an annual measure for year-round sea ice anomalies of the Southern Ocean and its regional sub-sectors. By relating selected years of significant sea ice conditions (1981, 2007 and 2014) with atmospheric influences, we demonstrate that the CSIAI is very useful for assessing inter-annular Antarctic SIC variability. Positive and negative sea ice anomalies can be qualitatively explained by atmospheric circulation anomalies in the years 1981 and 2007. However, in 2014, the year with the largest observed sea ice extent in our time series, we found that this positive sea ice anomaly was surprisingly not associated with a stationary and inter-seasonally persistent pattern of circulation anomaly. This suggests that sub-seasonal to seasonal circulation anomalies and ocean-related processes favoured the formation of the sea ice maximum in 2014. With this study we provide additional information on the long-term annual SIC variability around Antarctica. Furthermore, our classification approach and its results have potential for application in the evaluation of sea ice model results.
CRIS-Team Scopus Importer:2020-10-30
Keywords: passive microwave data; sea ice climatology; sea ice trends; sea ice variability

Global time series and temporal mosaics of glacier surface velocities derived from Sentinel-1 data - Friedl, Peter; Seehaus, Thorsten; Braun, Matthias (Earth System Science Data, 2021)
Consistent and continuous data on glacier surface velocity are important inputs to time series analyses, numerical ice dynamic modeling and glacier mass flux computations. Since 2014, repeat-pass synthetic aperture radar (SAR) data have been acquired by the Sentinel-1 satellite constellation as part of the Copernicus program of the EU (European Union) and ESA (European Space Agency). It enables global, near-real-time-like and fully automatic processing of glacier surface velocity fields at up to 6 d temporal resolution, independent of weather conditions, season and daylight. We present a new global data set of glacier surface velocities that comprises continuously updated scene-pair velocity fields, as well as monthly and annually averaged velocity mosaics at 200 m spatial resolution. The velocity information is derived from archived and new Sentinel-1 SAR acquisitions by applying a well-established intensity offset tracking technique. The data set covers 12 major glacierized regions outside the polar ice sheets and is generated in an HPC (high-performance computing) environment at the University of Erlangen-Nuremberg. The velocity products are freely accessible via an interactive web portal that provides capabilities for download and simple online analyses: http://retreat.geographie.uni-erlangen.de (last access: 6 October 2021). In this paper, we give information on the data processing and how to access the data. For the example region of Svalbard, we demonstrate the potential of our products for velocity time series analyses at very high temporal resolution and assess the quality of our velocity products by comparing them to those generated from very high-resolution TerraSAR-X SAR and Landsat-8 optical (ITS_LIVE, GoLIVE) data. The subset of Sentinel-1 velocities for Svalbard analyzed in this paper is accessible via the GFZ Potsdam Data Services under the DOI https://doi.org/10.5880/fidgeo.2021.016 (Friedl et al., 2021). We find that Landsat-8 and Sentinel-1 annual velocity mosaics are in an overall good agreement, but speckle tracking on Sentinel-1 6 d repeat acquisitions derives more reliable velocity measurements over featureless and slow-moving areas than the optical data. Additionally, uncertainties of 12 d repeat Sentinel-1 mid-glacier scene-pair velocities have less than half (< 0.08 m d−1) of the uncertainties derived for 16 d repeat Landsat-8 data (0.17–0.18 m d−1).

Grounding Line Retreat and Ice Discharge Variability at Two Surging, Ice Shelf-Forming Basins of Flade Isblink Ice Cap, Northern Greenland - Möller, Marco; Friedl, Peter; Palmer, Steven J.; Marzeion, Ben (Journal of Geophysical Research F: Earth Surface, 2022)
Ice discharge from Flade Isblink ice cap (NE Greenland) maintains an ice shelf at the northwestern fringe of the ice cap. The two outlet basins feeding this ice shelf surged during the late 1990s. Ice shelves are rare in Greenland and surges of ice shelf terminating glaciers even rarer. Understanding and explaining the evolution of ice mass changes in the two basins is hampered by a lack of knowledge about processes at their grounding zones. We determined, for the first time, the grounding line locations of these basins and analyzed their variability with time. We further quantified ice discharge and its variability during the period 1988–2020. We found that the grounding lines advanced slightly between 1993 and 1999 during the glacier surges, but showed overall retreats of 2.2 ± 1.3 km in basin 2 and 2.7 ± 0.9 km in basin 3 until 2019 over retrograde sloping beds. The retreats were promoted by increasing buoyancy forces due to increasing water depth, but opposing buttressing forces of the ice shelf induced a differing response of the grounding line in the two basins. Based on the observed patterns of flow and retreat, we characterized the surges as “Svalbard-type”, modified by buttressing effects of the ice shelf. We calculated total ice discharges over the study period of 1.85 ± 1.59 Gt in basin 2 and 1.38 ± 1.22 Gt in basin 3. We observed reductions in ice discharge of at least 90% after the surges, that persisted for the remainder of the period studied.
CRIS-Team Scopus Importer:2022-03-04
Keywords: Greenland; grounding line; ice cap; ice discharge; ice shelf

Recent dynamic changes on Fleming Glacier after the disintegration of Wordie Ice Shelf, Antarctic Peninsula - Friedl, Peter; Seehaus, Thorsten; Wendt, Anja; Braun, Matthias; Hoeppner, Kathrin (Cryosphere, 2018)

Remote sensing of glacier and ice sheet grounding lines: A review - Friedl, Peter; Fluhrer, Antje; Weiser, S.; Braun, Matthias (Earth-Science Reviews, 2020)
The precise positioning and long-term monitoring of the grounding line, forming the boundary between grounded and floating ice of marine ice sheets and tidewater glaciers, is critical for assessing ice sheet/glacier stability, ice sheet/glacier mass balance calculations and numerical ice modelling. However, mapping of the grounding line is a challenging task, since it is a subglacial and transient feature. Remote sensing techniques do not map the grounding line directly but locate surface features in the grounding zone that serve as proxies for the true grounding line position. The large variety of methods, products and publications, as well as an inconsistent use of terminology additionally complicate the topic. We present the first detailed review of existing remote sensing techniques and data for grounding line mapping. Benefits and limitations of the different techniques and data sources are discussed and illustrated with examples. We identify a present tradeoff between accuracy and both spatial coverage and temporal resolution of the derived grounding line products. Rather new methods like Sentinel-1-SAR (Synthetic Aperture Radar) Differential Range Offset Tracking (DROT) and Pseudo Crossover Radar Altimetry (PCRA) offer the potential for recent measurements and to fill gaps in some areas. Nevertheless, there is a high demand of new spaceborne radar sensors that provide time series of very short repeat pass data to enable regular grounding line monitoring with most accurate Differential SAR Interferometry (DInSAR) on a continental scal

Remote sensing of glacier and ice sheet grounding lines: A review - Friedl, Peter; Weiser, Frank; Fluhrer, Anke; Braun, Matthias (Earth-Science Reviews, 2019)

Spatial and Temporal Variability of Glacier Surface Velocities and Outlet Areas on James Ross Island, Northern Antarctic Peninsula. - Lippl, Stefan; Friedl, Peter; Kittel, Christoph; Marinsek, Sebastiàn; Seehaus, Thorsten; Braun, Matthias (Geosciences, 2019)
The northern Antarctic Peninsula was affected by a significant warming over the second half of the 20th century and the collapse of several ice shelves. Local climate conditions on James Ross Island on the northeastern coast can differ strongly from the main part of the Antarctic Peninsula. This paper reports the spatial and temporal variability of glacier surface velocities and the area of their outlets throughout James Ross Island, and evaluates potential relationships with atmospheric and oceanic conditions. Velocity estimates were retrieved from intensity feature tracking of scenes from satellite synthetic aperture radar sensors TerraSAR-X and TanDEM-X between 2014 and 2018, which were validated against ground observations. Calving front positions back to 1945 were used to calculate outlet area changes for the glaciers by using a common-box approach. The annual recession rates of almost all investigated glacier calving fronts decelerated for the time periods 2009–2014 and 2014–2018 in comparison to the period 1988–2009, but their velocity patterns differed. Analysis of atmospheric conditions failed to explain the different patterns in velocity and area changes. We suggest a strong influence from local bathymetric conditions. Future investigations of the oceanic conditions would be necessary for a profound understanding of the super-position of different influencing factor
Keywords: James Ross Island; Antarctic Peninsula; glacier velocities; glacier area changes